2022
DOI: 10.1093/brain/awac388
|View full text |Cite
|
Sign up to set email alerts
|

Using in vivo functional and structural connectivity to predict chronic stroke aphasia deficits

Abstract: Focal brain damage caused by stroke can result in aphasia and advances in cognitive neuroscience suggest that impairment may be associated with network-level disorder rather than just circumscribed cortical damage. A number of studies have shown meaningful relationships between brain-behaviour using lesions; however only a handful of studies have incorporated in-vivo structural and functional connectivity. Patients with chronic post-stroke aphasia were assessed with structural (N = 68) and functional (N = 39) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 82 publications
0
3
0
Order By: Relevance
“…These include, for example, premorbid brain atrophy (Levine et al, 1986), burden of white matter hyperintensities (Kamakura et al, 2017), fractional anisotropy values (Lunven et al, 2015), anosognosia (Stone et al, 1992), acute visual field defects (Samuelsson et al, 1997), acute allocentric (but not egocentric) neglect severity (Moore et al, 2021), as well as activation patterns and functional connectivity (Cao et al, 2022; Umarova et al, 2016). Changes in structural connectivity might also play a role (see Talozzi et al, 2023), although, for post-stroke aphasia, this measure could not add predictive value to models using the lesion information itself (Halai et al, 2020; Zhao et al, 2023). Future studies should investigate whether (some of) these or other potentially prognostic factors can add predictive information to the best-performing model(s) of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…These include, for example, premorbid brain atrophy (Levine et al, 1986), burden of white matter hyperintensities (Kamakura et al, 2017), fractional anisotropy values (Lunven et al, 2015), anosognosia (Stone et al, 1992), acute visual field defects (Samuelsson et al, 1997), acute allocentric (but not egocentric) neglect severity (Moore et al, 2021), as well as activation patterns and functional connectivity (Cao et al, 2022; Umarova et al, 2016). Changes in structural connectivity might also play a role (see Talozzi et al, 2023), although, for post-stroke aphasia, this measure could not add predictive value to models using the lesion information itself (Halai et al, 2020; Zhao et al, 2023). Future studies should investigate whether (some of) these or other potentially prognostic factors can add predictive information to the best-performing model(s) of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Feature selection may be a promising option to identify the most predictive variable combination. However, some research already indicated that lesion-induced disconnectivity might be unable to give further information in addition to lesion anatomy, since 26 the former is dependent on the latter (Halai et al, 2020;Hope et al, 2018;Zhao et al, 2023). On the other hand, a very recent investigation revealed that the combination of structural and functional disconnectivity (and demographics) achieved more accurate predictions than models with either one of them (and demographics) (Petersen et al, 2024).…”
Section: The Role Of Structural Disconnections In Predictive Modelingmentioning
confidence: 99%
“…During the non-acute stroke stage, survivors continue to undergo a dynamic process of functional reorganization associated with post-stroke recovery [ 1 , 2 ]. Resting-state fMRI has emerged as a promising avenue to explore brain functional integration and separation after stroke [ 3 ]. Our prior resting-state fMRI studies found decreased functional connectivity (FC) between hippocampal subfields and left postcentral gyrus as well as right middle occipital gyrus [ 4 ], between cerebellum posterior lobe and left precentral gyrus, inferior frontal gyrus as well as middle temporal gyrus [ 5 ], and increased FC from the ipsilesional primary motor cortex to the ipsilesional occipital lobes [ 6 ] in non-acute stroke patients compared with healthy controls (HCs).…”
Section: Introductionmentioning
confidence: 99%